COVID-19 associated vasculitis: A systematic review of case reports and case series. (February 2022) - Wong, Kalai; Farooq Alam Shah, Mir Umer; Khurshid, Maman; Ullah, Irfan; Tahir, Muhammad Junaid; Yousaf, Zohaib
Abstract: Vasculitis is one of the complications of COVID-19. We conducted a systematic review analysing the association of COVID-19 with vasculitis. We searched Google Scholar and PubMed from December 1, 2019, to October 11, 2021. The review included 8 studies (7 case reports and 1 case series) reporting 9 cases of vasculitis secondary to COVID-19. The mean age was 29.17 ± 28.2 years, ranging from 6 months to 83 years. The male to female ratio was 4:5. Maculopapular, violaceous, papular and erythematous rash were common. Heparin(n = 2), corticosteroids (n = 6) (methylprednisolone) and intravenous immunoglobulin (n = 4) were prescribed in these patients. Significant clinical improvement was observed in 8 out of 9 patients. One person died during treatment. Our study discusses vasculitis as one of the complications of COVID-19. Furthermore, the pathophysiology, clinical presentation, and management of COVID-19 associated vasculitis is discussed. Highlights: This is a systematic review of all published cases of vasculitis secondary to COVID-19 from the start of COVID-19 outbreak to date. Most common forms of vasculitis reported were Kawasaki disease Vasculitis, IgA vasculitis and Leucocytoclastic Vasculitis with symptoms being predominantly skin limited. Steroids, LMWH and IVIG were the most common line of treatment. An good overall prognosis was seen following treatment.